O efeito da infecção por Toxoplasma gondii em camundongos gestantes CB10-H2 (H-2b) e C57BL/KsJ (H-2d) - Coutinho, Loyane Bertagnolli (2016)
Successful pregnancy is related to Th2 immune response profile, including molecules encoded by the major histocompatibility complex (MHC); however, Toxoplasma gondii infection induces Th1 immune response that is associated with adverse pregnancy outcome. To investigate the influence of MHC haplotype in pregnancy outcome in T. gondii-infected animals, congenic mice, C57BL/KsJ and CB10-H2 females, were orally infected with ME-49 strain on the first day of pregnancy and sacrificed on 8 and 18 days post-infection. C57BL/KsJ showed higher number of parasites in the lungs at 8dI, irrespective of pregnancy, compared with CB10-H2; and both CB10-H2 and C57BL/KsJ showed high number of parasites in the brain at 18dI, irrespective of pregnancy. Parasites were not found in the uterus/placenta in both lineages of mice irrespective of the day of infection and there was no difference in abortion rate of infected mice, although CB10-H2 mice presented higher histological damage compared with C57BL/KsJ at 8 and 18 days of pregnancy and infection. Infection of non-pregnant C57BL/KsJ increased mast cell infiltration in the uterus, and gestation decreased this cell numbers. Furthermore, C57BL/KsJ presented higher IFN-γ levels systemically on 8dI; and TNF and IL-6 on 8 and 18dI compared with CB10-H2, despite gestation or not. Additionally, in the uterus/placenta of CB10-H2, pregnancy increased FOXP3 and under infection IL-10, IL-13 and IL-17 expression levels. Our data suggest that both genetic background and MHC haplotypes are essential to protect against reabsorption rate and abortion in congenital toxoplasmosis.